Dampak Keberadaan Pasar Modern Terhadap Pedagang Pasar Tradisional - Sugiyanto, Sukesi (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The existence of modern market toward traditional market is not only becomes the attention for the government of Balikpapan city but it has been becoming national issue that also get serious notice from the central government, so that central government publishes President Role No. 112 Tahun 2007 about structuring and developing relationship of central shopping traditional market and modern shop. So that’s why the existence of modern market needs a considerable study in order to be known how about the influence of its existence toward traditional market’s seller. This study is done to identify the position of traditional market and modern market from the institutional aspect and valid legislation point of view, knowing the effect of modern market’s presence toward traditional market work, and to arrange a concept of work ensnaring of ritel trading that can be applied to traditional market.            This is study is done in theterritoryofBalikpapancity. To support the growth and the development of both trading device that is traditional market and modern market, in order to both of them don’t turn out each other so the things that need to be done by The Government of Balikpapan city, controlling the location of modern market, controlling the modern market’s management, ensnaring traditional trader, and increasing the institutional of market. Key word: traditional market, modern market, and ensnaring traditional trader.